2023
DOI: 10.1101/2023.01.30.526320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamentals of biofilm formation in soil: From functionalized self-assembled monolayers to rewilding

Abstract: Surface energy and surface charges play crucial roles in bacterial adhesion and biofilm formation, however the mechanisms underlying the bacteria-surface interaction, particularly on the formation of soil biofilms, remain unclear. In spite of considering the spatiotemporal dynamics of biofilm formation on different soil surfaces, we compared the impact of four different substrates on bacterial attachment and biofilm formation. The substrates were constituted of gold layer covered by NH2+, CH3, COO- and OH-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Substrate topography is a key determinant of biofilm formation [60] [64-66] that with reason can be expected to vary among different types of minerals. With the use of gold substrate terminated with self-assembled monolayers of various chemicals, we also previously found that positively charged and hydrophobic particles support biofilm formation, while negative surface charge and hydrophilic particles resist bacterial communities to congregate [67]. The strong attraction to positive charged surfaces and vice versa repulsion to negative charged particles, can potentially be explained by the general net negative charge of bacterial cells [68, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Substrate topography is a key determinant of biofilm formation [60] [64-66] that with reason can be expected to vary among different types of minerals. With the use of gold substrate terminated with self-assembled monolayers of various chemicals, we also previously found that positively charged and hydrophobic particles support biofilm formation, while negative surface charge and hydrophilic particles resist bacterial communities to congregate [67]. The strong attraction to positive charged surfaces and vice versa repulsion to negative charged particles, can potentially be explained by the general net negative charge of bacterial cells [68, 69].…”
Section: Resultsmentioning
confidence: 99%